Achilles Pathology and Surgical Approach Determine Post-Operative Infection Rate. Issue 1 (January 2022) - Rider, Carson M.; Hansen, Oliver B.; Drakos, Mark C.
Category: Sports; Other Introduction/Purpose: Post-operative infections can be a devastating complication after Achilles tendon surgery. While Achilles infection rates have decreased with the development of less invasive surgical techniques, these infections remain a challenging complication for patients and clinicians due to the relative lack of vasculature in the Achilles tendon region. This study aimed to analyze rates of postoperative Achilles tendon infection based on the type of Achilles pathology and surgical approach. We hypothesized that procedures with smaller incisions that avoided the critical zone would be associated with lower infection rates than those that require larger incisions, such as reconstructions. Methods: All patients undergoing Achilles tendon surgery at a single, multi-surgeon center between 2011 and 2020 were identified. Charts were reviewed for infection, pathology, surgical approach, incision size, and risk factors such as body mass index (BMI), smoking status, and diabetes. Rates of infection were compared between groups based on pathology and operative technique. These groups included acute rupture treated immediately, chronic pathology treated with debridement and repair, and chronic pathology treated with graft reconstruction. For patients treated for an acute rupture, minimally invasive and open approach sub-groups were compared. Further, prevalence of risk factors was compared between patients with and without post- operative infections. Statistical comparisons were performed between groups using a student's t-test or Fisher's exact test. Results: A total of 1, 148 cases were identified, 23 of which involved a post-operative infection requiring a return to the operating room for irrigation and debridement. The overall infection rate was 2.00%. Cases involving chronic pathology treated with graft reconstruction were associated with an infection rate of 8.96%. Acute repairs had an infection rate of 1.32% and other chronic pathologies treated without graft reconstruction had an infection rate of 0.73%. Statistical comparisons of infection rates for these sub-groups are displayed in Table 1 alongside comparisons of risk factor prevalence between the infection and non-infection groups. The comparison of risk factors between groups did not identify any significant differences. No infections were observed following the use of a distal lateral incision to treat chronic tendon pathology (179 cases) or the use of a windows incision technique for reconstructions (8 cases). Conclusion: Analysis of infection rates indicated that treatment options requiring large incisions, such as reconstruction with a graft, pose a significantly greater risk of post-operative Achilles infection. Both minimally invasive treatments and measured open incisions were associated with similarly low infection rates for primary repair of acute ruptures. Comparison of risk factors between patients with and without infection did not reveal any significant differences. Given low infection rates for chronic pathology treated with distal lateral incisions and windows-type incisions, we recommend these whenever possible.